Life crossing a commercial/recreational bridge - Ollero, Joaquin Benedetto P.; Evangelista, Alex Ray P. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
Life Crossing is a commercial and recreational bridge traversing the Pasig River - connecting the cities of Makati and Mandaluyong. The idea is to combine commercial and recreational spaces with infrastructure. Infrastructure projects such as bridges have potential. The bridge + space envisions the bridge such that the people is given unequal and even more importance than the car - focusing the development on the people rather than the car. JICA in partnership with NEDA developed the Roadmap for Infrastructure Development for Metro Manila and its Surrounding Areas. One of its projects is the C3 Missing Link Path; a project aimed to build the missing link of the road network. It traverse the Pasig River which is the site of the project. The spaces of the project includes shops, market stalls, a rock climbing facility, parkour space, parks, a skate park and a jogging path - aimed to cater to the lifestyle of the nearby community. In conclusion, Life Crossing is a project that look the underutilized bridge and its potential - by adding spaces and created a better environment for the occupant, the community, and its city.
includes appendices
Best Thesis (Arch) AY 2015-2016, 2nd place
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Bridges -- Designs and plans